2015
DOI: 10.5539/ijb.v7n4p13
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nutritional Composition of Encosternum delegorguei Caught in Nerumedzo Community of Bikita, Zimbabwe

Abstract: Three forms of Encosternum delegorguei consumed in Nerumedzo community, Bikita, Zimbabwe were analysed for their nutritional composition. Protein, fat, ash and mineral content were determined for the preprocessed, well prepared and spoiled bugs. The proximate composition and minerals of the insects were determined using standard methods. One Way Analysis of Variance (ANOVA) was used in analyzing data. They were found to contain 30-36% protein; 51-53% fat and 1-1.5% ash respectively. Spoiled bugs contained the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…All samples were oven-dried at 60-70°C for 12-24 hours (Makore, Garamumhango, Chirikure, & Chikambi, 2015;Tiroesele, Seletlo, & Moreki, 2013). Dry specimens were grounded separately and each specimen weighed 100 g for proximate analysis purposes.…”
Section: B Methodsmentioning
confidence: 99%
“…All samples were oven-dried at 60-70°C for 12-24 hours (Makore, Garamumhango, Chirikure, & Chikambi, 2015;Tiroesele, Seletlo, & Moreki, 2013). Dry specimens were grounded separately and each specimen weighed 100 g for proximate analysis purposes.…”
Section: B Methodsmentioning
confidence: 99%
“…In addition to being a healthy appetizer, the stinkbug has acclaimed traditional medicinal values, such as decreasing hypertension and curing asthma and heart diseases 154 . Likewise, the Chinese stinkbug, Aspongopus chinensis (Pentatomidae), is a nutrient-rich edible insect which has been employed to relieve pain, and treat nephropathy and kidney disease in China.…”
Section: Hemiptera (True Bugs Aphids Cicadas and Scale Insects)mentioning
confidence: 99%
“…The stinkbug Encosternum delegorguei (Tessaratomidae), an edible treat in Zimbabwe and South Africa, was recently proven to contain significant amounts of protein, fat and minerals validating its use as a nutritional food source 153 , 154 . In addition to being a healthy appetizer, the stinkbug has acclaimed traditional medicinal values, such as decreasing hypertension and curing asthma and heart diseases 154 . Likewise, the Chinese stinkbug, Aspongopus chinensis (Pentatomidae), is a nutrient-rich edible insect which has been employed to relieve pain, and treat nephropathy and kidney disease in China.…”
Section: Hemiptera (True Bugs Aphids Cicadas and Scale Insects)mentioning
confidence: 99%
“…Insects are recognized as a rich source of pharmaceuticals due to their various therapeutic properties such as analgesic, immunological, diuretic, antibacterial, antirheumatic, and anesthetic effects. Insects have been identi ed as a natural source for treating and preventing a diverse range of ailments, including HIV, bacterial infections, hypertension, cancer, asthma, cardiovascular disease, and nephropathy [15]. Multiple studies have demonstrated the potential therapeutic bene ts of insects like Aspongopus chinensis, Aspongopus vidiuatus, Blattella, Kerrialacca, Agonoscelis pubescens, and Phyllophaga in treating epilepsy, rheumatism, scabies, macula, measles, and dermatological problems [16].…”
Section: Introductionmentioning
confidence: 99%